Penggunaan ZnO/Zeolit Sebagai Katalis Dalam Degradasi Tartrazin Secara Ozonolisis - Zilfa, Zilfa; Safni, Safni; Rahmi, Febi (Universitas Andalas, 2021)
An investigation on modification of natural zeolite with ZnO for the degradation of tartrazine. In this study, ZnO as a semiconductor is modified into a natural zeolite as support to form ZnO/zeolite that can increase the efficiency degradation of tartrazine. Further, the formed catalyst was added to tartrazine by determining the variation in ozonolysis time, the amount of addition of the catalyst, and the addition of a catalyst time. The results of degradation were determined by UV-Vis spectrophotometer at 424 nm. The result showed that the percentage of degradation obtained on each catalyst in the degradation. The resulted percent degradation of 20 ml of tartrazine at concentration of 15 mg/L using 20 mg ZnO/zeolite was 56.80%, while using 0.77 mg ZnO was 42.25%, and with the addition of 19.23 mg of Zeolite was 31.18%, all of that condition was proceeded by 40 minutes of ozonolysis. Thus, the result indicates that the ZnO/zeolite catalyst can increase percentages of tartrazine degradation by ozonolysis. It is known that the catalyst ZnO/zeolite is very effective in increasing the degradation of tartrazine. Analysis of tartrazine compounds using fourier-transform infrared spectroscopy (FTIR) after degradation changes in wavenumber indicates that there is a breaking of the bonds of tartrazine compounds. Characterization of ZnO/zeolite catalyst using FTIR, X-Ray diffraction (XRD) and scanning electron microscope (SEM), in each spectrum there was no shift, indicating that there is no change in ZnO/zeolite structure